Lipid Bilayer–mediated Regulation of Ion Channel Function by Amphiphilic Drugs - Lundbaek, Jens A (The Journal of general physiology, 2008)
Drugs that at pico- to nanomolar concentration regulate ion channel function by high-affinity binding to their cognate receptor often have a "secondary pharmacology," in which the same molecule at low micromolar concentrations regulates a diversity of membrane proteins in an apparently nonspecific manner. It has long been suspected that this promiscuous regulation of membrane protein function could be due to changes in the physical properties of the host lipid bilayer, but the underlying mechanisms have been poorly understood. Given that pharmacological research often involves drug concentrations that alter the physical properties of lipid bilayers, and that nonspecific drug effects are a major cause of attrition in drug discovery, this lack of understanding has been problematic. The present Perspective summarizes recent developments in the investigation of the bilayer-mediated mechanism that are transforming it into a subject of quantitative science. It is described how the hydrophobic interactions between a membrane protein and the host lipid bilayer provide the basis for a mechanism, whereby protein function is regulated by the bilayer physical properties. The use of gramicidin channels as single-molecule force transducers for measuring drug-induced changes in the bilayer physical properties (bilayer stiffness), and for predicting drug effects on membrane protein function, is described. [PUBLICATION ABSTRACT]